DNS analysis of small-scale turbulence-scalar interactions in evaporating two-phase flows. (October 2016) - Bouali, Zakaria; Duret, Benjamin; Demoulin, François-Xavier; Mura, Arnaud
Highlights: Direct Numerical Simulation (DNS) of turbulent two-phase flows are conducted. A detailed investigation of the turbulence-scalar interaction (TSI) term is performed. The topology of the scalar field is modified as the liquid/gas interface is approached. In this zone the orientation of the scalar field tends to minimize the TSI. Abstract: Scalar dissipation rate (SDR) is a key quantity in turbulent flow modeling since it measures the scalar mixing intensity. It is well known that turbulence-scalar interaction (TSI) processes play an essential role in turbulent scalar mixing and drive to a large extent the SDR evolution. These processes are characterized by the tensor inner product between the scalar gradient vector and the strain-rate tensor. Direct numerical simulations are conducted to analyze the physics of this interaction in vaporizing turbulent two-phase flows. The well known alignment of the scalar gradient with the most compressive principal direction of the strain-rate tensor – resulting in production of the scalar gradient by turbulence – is recovered in statistics collected sufficiently far from the liquid–gas interface. By contrast, the action of the turbulence-scalar interaction is progressively attenuated as we approach this interface, where the scalar gradient tends to have a direction intermediate between the extensive and the compressive directions. This result questions the validity of passive-scalar turbulence concepts and closures that are commonly used for to tackle the modeling of scalar behavior in vaporizing two-phase flows featuring (or not) subsequent chemical reactions.